Effect of Plasmid DNA Size on Chitosan or Polyethyleneimine Polyplexes Formulation - Valente, J. F. A. (2021)
Gene therapy could be simply defined as a strategy for the introduction of a functional copy of desired genes in patients, to correct some specific mutation and potentially treat the respective disorder. However, this straightforward definition hides very complex processes related to the design and preparation of the therapeutic genes, as well as the development of suitable gene delivery systems. Within non-viral vectors, polymeric nanocarriers have offered an ideal platform to be applied as gene delivery systems. Concerning this, the main goal of the study was to do a systematic evaluation on the formulation of pDNA delivery systems based on the complexation of different sized plasmids with chitosan (CH) or polyethyleneimine (PEI) polymers to search for the best option regarding encapsulation efficiency, surface charge, size, and delivery ability. The cytotoxicity and the transfection efficiency of these systems were accessed and, for the best p53 encoding pDNA nanosystems, the ability to promote protein expression was also evaluated. Overall, it was showed that CH polyplexes are more efficient on transfection when compared with the PEI polyplexes, resulting in higher P53 protein expression. Cells transfected with CH/p53-pDNA polyplexes presented an increase of around 54.2% on P53 expression, while the transfection with the PEI/p53-pDNA polyplexes resulted in a 32% increase.